PENGARUH AIR LAUT, ZEOLIT, DAN PASIR VULKAN TERHADAP STATUS HARA PADA TANAH GAMBUT SERTA PERTUMBUHAN DAN PRODUKSI PADI SAWAH - Ahmad Taufik Lubis; Zulkifli Nasution; Sarifuddin Sarifuddin (Universitas Sumatera Utara, 2013)
ABSTRACTThe objective of this research is to improve the chemical properties of peat soil for increasing riceproductivity. The research using factorial randomized block design with 2 factors and 3 replications,consist of a) sea water, and b) mineral materials (zeolite and volcanic material). Mineral materials(M) consist of without mineral materials (M0), 2% zeolite mineral soil samples (200 gram/pot)(M1), volcanic material as much as 10% (1000 gram/pot) (M2), and mixture of zeolite minerals andvolcanic material (M3). Sea water like without sea water (0%) (A0), 25%v/v consentration of seawater (A25), 50% v/v consentration of sea water (A50), and 75%v/v consentration of sea water (A75).The results showed that the application of mineral zeolite and volcanic material significantlyincreased soil pH concentration, P- available, bulk density, dry weight of the canopy and root dryweight. Sea wate significantly decreased pH, cation exchange capacity, shoot and root dry weight,increasing electrical conductivity, base saturation but increasing P- available not significantly onempty grain and weight of 1000 grains.Keywords : sea water, zeolite, volcanic material, peat soil, and paddy